2020
DOI: 10.1177/2331216520960601
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Speech Recognition With a Cochlear Implant and Increased Perceptual and Cognitive Demands

Abstract: Speech recognition in complex environments involves focusing on the most relevant speech signal while ignoring distractions. Difficulties can arise due to the incoming signal’s characteristics (e.g., accented pronunciation, background noise, distortion) or the listener’s characteristics (e.g., hearing loss, advancing age, cognitive abilities). Listeners who use cochlear implants (CIs) must overcome these difficulties while listening to an impoverished version of the signals available to listeners with normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Processing speed is the time required to complete a mental task ( Kail and Salthouse, 1994 ). To test this, one task is used that also assesses attention: the “WJ-IV letter and number pattern matching task and the pair cancelation task.” Furthermore, the “Wechsler Adult Intelligence Scale III (WAIS-III) symbol search.” the “NIH toolbox pattern comparison processing speed test”, the “WAIS-III coding test” and the “WJ-IV numbers reversed test” are used (see Table 5b for an overview) ( Hillyer et al, 2019 ; Mussoi and Brown, 2019 ; Tinnemore et al, 2020 ). Of all of these tests only the pattern comparison test showed a significant relationship with sentences in quiet ( p = 0.006) ( Tinnemore et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Processing speed is the time required to complete a mental task ( Kail and Salthouse, 1994 ). To test this, one task is used that also assesses attention: the “WJ-IV letter and number pattern matching task and the pair cancelation task.” Furthermore, the “Wechsler Adult Intelligence Scale III (WAIS-III) symbol search.” the “NIH toolbox pattern comparison processing speed test”, the “WAIS-III coding test” and the “WJ-IV numbers reversed test” are used (see Table 5b for an overview) ( Hillyer et al, 2019 ; Mussoi and Brown, 2019 ; Tinnemore et al, 2020 ). Of all of these tests only the pattern comparison test showed a significant relationship with sentences in quiet ( p = 0.006) ( Tinnemore et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…They showed that performance on this task significantly differed between better and poorer performers on a word task in quiet (Cohen's d = 0.58, p = 0.037) (Völter et al, 2021). However, the performance did not significantly predict performance for sentence perception in quiet (Tinnemore et al, 2020).…”
Section: Cognitive Inhibitionmentioning
confidence: 97%
See 1 more Smart Citation
“…Perhaps a simulation of 6-channel vocoded speech would have better matched performance between the two listener groups. Alternatively, one-to-one matching of listeners by age and performance could be done ( Bhargava et al, 2016 ; Tinnemore et al, 2020 ). Choosing a simulation that perfectly matches performance, however, is complicated by the differences in experience listening to spectrally degraded speech, since performance can change over exposure time (e.g., Rosen et al, 1999 ; Davis et al, 2005 ; Smalt et al, 2013 ; Waked et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, speech perception in normal hearing (vocoded) and cochlear implant listeners differs when the spectral degradation is convolved with additional degradation in the input signal, e.g., when the speech is accented. While the speech recognition performance is better in CI over NH (vocoded) listeners when listening to unaccented speech, this pattern of performance reverses when speech is accented (Tinnemore et al, 2020). Future studies could therefore aim to address some of these issues by combining noise-vocoding with pitch shifting, to establish how Running head: Use of visual cues during adaptation to noise-vocoded speech 31 listeners perceive and adapt to a more direct representation of the percept likely experienced by people with a cochlear implant.…”
Section: Av Mouth Eyes and Block Conditionsmentioning
confidence: 96%